1999
DOI: 10.1177/0310057x9902700202
|View full text |Cite
|
Sign up to set email alerts
|

Clonidine and Cardiac Surgery: Haemodynamic and Metabolic Effects, Myocardial Ischaemia and Recovery

Abstract: Clonidine may have beneficial effects in patients undergoing major surgery. We enrolled 156 patients having elective CABG surgery in a double-blind, randomized trial. Patients were randomized to receive either two doses of placebo (Group PP) or clonidine 5 µg/kg (Group CC). Perioperative measurements included haemodynamics, anaesthetic and analgesic drug usage, creatinine clearance, cortisol excretion, recovery times and quality of life (SF-36) after surgery. Overall, there was no significant difference with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 30 publications
0
28
0
1
Order By: Relevance
“…Substantial reductions in the need for various anaesthetics have been demonstrated following administration of clonidine in patients undergoing either cardiac or non-cardiac surgery [33][34][35][36][37]. In patients undergoing CABG surgery, a 45% reduction in the dose of fentanyl needed to reach a similar level of anaesthetic depth was observed when clonidine was given as premedication [36].…”
Section: Anaesthetic-and Analgesic-sparing Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial reductions in the need for various anaesthetics have been demonstrated following administration of clonidine in patients undergoing either cardiac or non-cardiac surgery [33][34][35][36][37]. In patients undergoing CABG surgery, a 45% reduction in the dose of fentanyl needed to reach a similar level of anaesthetic depth was observed when clonidine was given as premedication [36].…”
Section: Anaesthetic-and Analgesic-sparing Effectsmentioning
confidence: 99%
“…In patients being prepared for surgery, use of clonidine was associated with reductions in BP and HR [33,68,69]. Haemodynamic lability was also attenuated [37,68,[70][71][72], though responses to intubation were not always blunted [33]. Patients premedicated with clonidine 5 µg kg Ϫ1 in preparation for CABG exhibited more favourable intraoperative 364 R. Aantaa and J. Jalonen Comparison of primary haemodynamic parameters in patients undergoing elective plastic surgery (n ϭ 30, ASA I) following premedication with dexmedetomidine (2.5 µg kg Ϫ1 ) or clonidine (4 µg kg Ϫ1 ).…”
Section: Intraoperative Sympatholytic/haemodynamic Effectsmentioning
confidence: 99%
“…Previous studies have shown that both mental and physical QoL decrease in patients between surgery and 1 month post-operatively. 11,38 Post-operative physical stress in the form of wound healing (chest wound and conduit graft harvesting sites), respiratory distress (pain on deep respiration and cough) is common. In addition, the mental stress associated from being in pain and feeling worse than prior to surgery, significantly decreases mental QoL.…”
Section: Quality Of Life Changesmentioning
confidence: 99%
“…Die Ergebnisse für die älteste verfügbare Substanz, das Clonidin, sind nicht einheitlich. Für herzchirurgische Patienten wurde keine wirksame Dämpfung der Stressantwort, sondern lediglich eine hämodynamische Stabilisierung gefunden [28,39]. Bei allgemeinchirurgischen Patienten ist eine Unterdrückung der postoperativ erhöh-ten Katecholaminkonzentrationen beschrieben, Auswirkungen auf kardiale Komplikationen wurden aber nicht beschrieben [12].Als neuere Substanz wurde das Mivazerol in großen multizentrischen Studien an Patienten mit KHK oder entsprechenden Risikofaktoren untersucht.…”
Section: Therapie Mit Alpha-2-agonistenunclassified